IgG and IgM titres Problems in Determining Diagnosis of Toxoplasmosis - soedarto, soedarto (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
To determine acute Toxoplasma gondii infection in pregnant women, is of interest worldwide due to the risk of congenital toxoplasmosis. Ability to diagnose recently acquired infection in the pregnant woman and congenital infection in the fetus and newborn was improved. Interpreting on maternal serological screening tests by new methodsÂ  should not rely on a single sample test but need confirmatory testing through a nationally recognized reference laboratory if results of serological tests are positive.